Perbandingan penggambaran tokoh Rahwana pada Candi Prambanan dan Candi Panataran: Perbandingan Penggambaran Tokoh Rahwana pada Candi Prambanan dan Candi Panataran dalam Perspektif Ikonografi Komparatif - Noer, Kyra Andhayu; Prasodjo, Tjahjono (Berkala Arkeologi, 2025)
This study discusses about the comparison of Rahwana depiction in reliefs of the Ramayana story found in Candi Prambanan (9th century) and Candi Panataran (14th century) through a comparative iconographic analysis based on Panofsky’s theory. Rahwana at Candi Prambanan is depicted in supernatural form, possessing multiple heads and hands in a naturalistic and ideal style. This depiction is rooted in classical Indian art which was later adapted by Old Javanese artists. This portrayal affirms royal legitimacy through association with the divine. In the other hand, Rahwana in Candi Panataran presents in a more rigid, wayang kulit (shadow puppet) form, as an ordinary human lacking mythological features. This representation serves as a political allegory, symbolizing real-world threats within the context of ancient Javanese society. These differences reflect a shift in both artistic style and symbolic meaning, as Rahwana transform form a mythic villain in Indian epic tradition to a political metaphor shaped by Javanese socio-political realities, emphasizing the differing historical backdrops of the two temple eras.